2015
DOI: 10.1097/md.0000000000001080
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram Derived QRS Duration >120 ms is Associated With Elevated Plasma Homocysteine Levels in a Rural Australian Cross-Sectional Population

Abstract: Homocysteine levels in the low to moderate range for cardiovascular risk have been previously associated with left ventricular cardiac hypertrophy (LVH). Electrocardiogram (ECG) derived QRS duration has also been used as an epidemiological screening marker for cardiac hypertrophy risk. QRS duration cut offs have not been previously modeled to assess homocysteine levels in community populations. Our aims are to determine if QRS duration is associated with an elevated homocysteine level in a cross-sectional Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Acampa found that, in OHT patients, plasma Hcy levels significantly correlated with PWD, whereas no correlation was found with the QTc interval [13]. Lee Yin Leng et al concluded that in community populations, homocysteine was moderately elevated when QRS durations were >120 ms, but QTc intervals were not significantly associated with plasma homocysteine [26]. In our study, Linear regression and multiple logistic regression analyses results showed an association between QTc interval and Hcy levels.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Acampa found that, in OHT patients, plasma Hcy levels significantly correlated with PWD, whereas no correlation was found with the QTc interval [13]. Lee Yin Leng et al concluded that in community populations, homocysteine was moderately elevated when QRS durations were >120 ms, but QTc intervals were not significantly associated with plasma homocysteine [26]. In our study, Linear regression and multiple logistic regression analyses results showed an association between QTc interval and Hcy levels.…”
Section: Discussioncontrasting
confidence: 44%
“…The QT interval is measured from the earliest detection of depolarization in any lead to the latest detection of repolarization in any lead. Since the QT interval is influenced by heart rate, it is necessary to adjust heart rate for QT correction [26]. In this study, the QTc interval was corrected for the heart rate using the Bazett formula, which is the most common method [2729].…”
Section: Methodsmentioning
confidence: 99%
“…Resting 12-lead electrocardiograms were obtained from each subject using a Welch Allyn PC-Based ECG system as previously described [ 4 ]. This permitted automated QRS duration calculation from a 10 s ECG trace.…”
Section: Methodsmentioning
confidence: 99%
“…Electrocardiogram (ECG) derived QRS durations >100 msec and >120 msec have been both associated with hypertension induced increases in left ventricular (LV) mass [ 1 – 4 ]. Myocardial hypertrophy can alter LV tissue repolarisation and slowing of transmural conduction velocity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our main findings do not support the hypothesis that R-R derived HRV parameters are associated with increasing QRS duration in non-diabetics. The QRS duration cut offs that we modeled would reflect both normal and underlying conduction disturbances observed in rural communities [ 6 , 16 ]. QRS duration greater than 120 msec in our cohort were most likely due to pre-existing cardiovascular disease, age related aortic stiffening, remodeling and or conduction slowing [ 6 ].…”
Section: Discussionmentioning
confidence: 99%